A new adsorption-elution technique for the concentration of aquatic extracellular antibiotic resistance genes from large volumes of water. (1st April 2016) - Wang, Da-Ning; Liu, Lu; Qiu, Zhi-Gang; Shen, Zhi-Qiang; Guo, Xuan; Yang, Dong; Li, Jing; Liu, Wei-li; Jin, Min; Li, Jun-Wen
Abstract: Extracellular antibiotic resistance genes (eARGs) that help in the transmission and spread of antibiotic-resistant bacteria are emerging environmental contaminants in water, and there is therefore a growing need to assess environmental levels and associated risks of eARGs. However, as they are present in low amounts, it is difficult to detect eARGs in water directly with PCR techniques. Here, we prepared a new type of nucleic acid adsorption particle (NAAP) with high capacity and developed an optimal adsorption-elution method to concentrate eARGs from large volumes of water. With this technique, we were able to achieve an eARG recovery rate of above 95% from 10 L of water samples. Moreover, combining this new method with quantitative real-time PCR (qPCR), the sensitivity of the eARG detection was 10 4 times that of single qPCR, with the detection limit lowered to 100 gene copies (GCs)/L. Our analyses showed that the eARG load, virus load and certain water characteristics such as pH, chemical oxygen demand (CODMn ), and turbidity affected the eARGs recovery rate. However, high eARGs recovery rates always remained within the standard limits for natural surface water quality, while eARG levels in water were lower than the detection limits of single qPCR assays. The recovery rates were not affected by water temperature and heterotrophic plate counts (HPC). The eARGs whatever located in the plasmids or the short-length linear DNAs can be recovered from the water. Furthermore, the recovery rate was high even in the presence of high concentrations of plasmids in different natural water (Haihe river, well water, raw water for drinking water, Jinhe river, Tuanbo lake and the Yunqiao reservoir). By this technology, eARGs concentrations were found ranging from (2.70 ± 0.73) × 10 2 to (4.58 ± 0.47) × 10 4 GCs/L for the extracellular ampicillin resistance gene and (5.43 ± 0.41) × 10 2 to (2.14 ± 0.23) × 10 4 GCs/L for the extracellular gentamicin resistance gene in natural water for the first time, respectively. All these findings suggest that NAAPs have great potential for the monitoring of eARGs pollution in water. Graphical abstract: Highlights: We present a technique for eARG recovery with 10 4 times more sensitive than qPCR. With our method, eARGs can be concentrated from large volume of water. We also describe novel nucleic acid adsorption particles with high capacity for eARGs. We determine eARGs concentration in natural water.